BKMT’s 4T Da’wah Strategy In Strengthening Islamic Brotherhood: A Case Study Of Teramang Jaya District, Mukomuko - Aprizal (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study aims to examine the da’wah strategy implemented by the Majelis Taklim Contact Body (BKMT) of Teramang Jaya District in strengthening Islamic brotherhood. Using a qualitative approach with descriptive methods, this study collected data through observation, interviews, and documentation from BKMT administrators and members. The results show that BKMT implements a holistic da’wah strategy called the 4T strategy, namely: Ta’aruf (getting to know each other), Tafahum (understanding each other), Ta’awun (helping each other), and Takafu (bearing each other). These four pillars are interconnected and have succeeded in creating a strong brotherhood among members. Despite inhibiting factors such as busy schedules and geographical challenges, this strategy is supported by solid management and active member participation. This study concludes that BKMT's 4T strategy is effective in establishing Islamic brotherhood at the local level, and provides an important contribution to the development of an adaptive non-formal da’wah model.